Dominant ER Stress–Inducing WFS1 Mutations Underlie a Genetic Syndrome of Neonatal/Infancy-Onset Diabetes, Congenital Sensorineural Deafness, and Congenital Cataracts - De Franco, Elisa (Diabetes, 2017)
Neonatal diabetes is frequently part of a complex syndrome with extrapancreatic features: 18 genes causing syndromic neonatal diabetes have been identified to date. There are still patients with neonatal diabetes who have novel genetic syndromes. We performed exome sequencing in a patient and his unrelated, unaffected parents to identify the genetic etiology of a syndrome characterized by neonatal diabetes, sensorineural deafness, and congenital cataracts. Further testing was performed in 311 patients with diabetes diagnosed before 1 year of age in whom all known genetic causes had been excluded. We identified 5 patients, including the initial case, with three heterozygous missense mutations in WFS1 (4/5 confirmed de novo). They had diabetes diagnosed before 12 months (2 before 6 months) (5/5), sensorineural deafness diagnosed soon after birth (5/5), congenital cataracts (4/5), and hypotonia (4/5). In vitro studies showed that these WFS1 mutations are functionally different from the known recessive Wolfram syndrome–causing mutations, as they tend to aggregate and induce robust endoplasmic reticulum stress. Our results establish specific dominant WFS1 mutations as a cause of a novel syndrome including neonatal/infancy-onset diabetes, congenital cataracts, and sensorineural deafness. This syndrome has a discrete pathophysiology and differs genetically and clinically from recessive Wolfram syndrome.